2020
DOI: 10.12750/jarb.35.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Canine amniotic membrane derived mesenchymal stem cells exosomes addition in canine sperm freezing medium

Abstract: Exosomes have been discovered in 1983 (Pan and Johnstone, 1983) and are defined as 40-100 nm extracellular vesicles originating from the fusion of multi-vesicular bodies, also referred to as late endosomes, with the plasma membrane. They are known to mediate cell-to-cell communication as they can carry proteins, nucleic acids, and lipids, providing through that cargo a paracrine effect to the recipient tissues or cells (Mitchell et al., 2019). Thus, stem cell-derived exosomes have been used as a shuttle in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…According to animal studies, exosomes appear to be a promising avenue to restore spermatogenesis and sperm regeneration; a study has shown that amniotic fluid-derived exosome can restore sperm parameters such as motility, concentration, as well as the number of spermatogonia, spermatocytes, and ultimately male fertility ( Mobarak et al, 2021 ). The protective effect of exosomes against sperm cryoinjuries (such as cell membrane injury, DNA damage) and oxidative stress produced by cryopreservation process and improvement of the post-thaw sperm parameters has been reported ( Qamar et al, 2019 ; Mahiddine et al, 2020 ). Interestingly, treatment of spermatozoa with MSC-derived exosomes, in addition to improving sperm parameters after frozen-thawed, can increase sperm adhesive and fusogenic properties by adhesion molecules shuttling such as CD44, CD29, CD54, and CD106 ( Mokarizadeh et al, 2013 ; Figure 2 ).…”
Section: Potential Therapeutic Role Of Mesenchymal Stem Cells-derived Exosome In Sperm Abnormalitymentioning
confidence: 99%
“…According to animal studies, exosomes appear to be a promising avenue to restore spermatogenesis and sperm regeneration; a study has shown that amniotic fluid-derived exosome can restore sperm parameters such as motility, concentration, as well as the number of spermatogonia, spermatocytes, and ultimately male fertility ( Mobarak et al, 2021 ). The protective effect of exosomes against sperm cryoinjuries (such as cell membrane injury, DNA damage) and oxidative stress produced by cryopreservation process and improvement of the post-thaw sperm parameters has been reported ( Qamar et al, 2019 ; Mahiddine et al, 2020 ). Interestingly, treatment of spermatozoa with MSC-derived exosomes, in addition to improving sperm parameters after frozen-thawed, can increase sperm adhesive and fusogenic properties by adhesion molecules shuttling such as CD44, CD29, CD54, and CD106 ( Mokarizadeh et al, 2013 ; Figure 2 ).…”
Section: Potential Therapeutic Role Of Mesenchymal Stem Cells-derived Exosome In Sperm Abnormalitymentioning
confidence: 99%
“…Methods used for analyzing sperm plasma membrane are normally based on the enhanced permeability of damaged membrane [ 107 ]. These methods include the hypo-osmotic swelling (HOS) test [ 108 , 109 ], eosinā€“nigrosin staining [ 110 , 111 ], and use of fluorescent probes [ 112 , 113 ]. Fluorescent probes such as Hoechst or propidium-iodide (PI) are either used alone or in combination with other permeable fluorochromes such as carboxyfluorescein diacetate or SYBR [ 114 ā€“ 116 ].…”
Section: Plasma Membrane Integritymentioning
confidence: 99%
“…The amplitude of lateral head displacement also improved in exosome-treated dog spermatozoa [137]. Interestingly, stem-cell-derived conditioned medium and exosomes improved motility, viability, mitochondrial activity, and membrane integrity post-thawing in canine semen cryopreservation [144,145].…”
Section: Effect Of Exosomes On Sperm Motility and Viabilitymentioning
confidence: 99%